1996
DOI: 10.1090/s0273-0979-96-00654-4
|View full text |Cite
|
Sign up to set email alerts
|

On some applications of automorphic forms to number theory

Abstract: Abstract. A basic idea of Dirichlet is to study a collection of interesting quantities {an} n≥1 by means of its Dirichlet series in a complex variable w: n≥1 ann −w . In this paper we examine this construction when the quantities an are themselves infinite series in a second complex variable s, arising from number theory or representation theory. We survey a body of recent work on such series and present a new conjecture concerning them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…See Bucur and Diaconu [19]. Nevertheless, the approach taken in [20], which we will next explain, shows that the multiple Dirichlet series cannot have meromorphic continuation to all s i and w if k > 3.…”
Section: Andmentioning
confidence: 96%
See 3 more Smart Citations
“…See Bucur and Diaconu [19]. Nevertheless, the approach taken in [20], which we will next explain, shows that the multiple Dirichlet series cannot have meromorphic continuation to all s i and w if k > 3.…”
Section: Andmentioning
confidence: 96%
“…In [20] a different approach was taken. If k > 3, then it may be possible to write down a correct definition of the multiple Dirichlet series, and indeed this has essentially been done in the very interesting special case k = 4.…”
Section: Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Such series first arose from the study of certain Hecke-RankinSelberg type integrals of metaplectic Eisenstein series (see [BFH1]), but it is not apparent that the series used here may be so-obtained. Instead, our work is based on the convexity principle for holomorphic functions of two complex variables, whose use to study such series was first observed by Bump,Friedberg and Hoffstein [BFH2].…”
Section: Introductionmentioning
confidence: 99%